Ag2Cu2O3- a catalyst template material for selective electroreduction of CO to C(2+)products - Marti, Nemanja; Reller, Christian; Macauley, Chandra; Löffler, Mario; Reichert, Andreas; Reichbauer, Thomas; Vetter, Kim-Marie; Schmid, Bernhard; Mclaughlin, David; Leidinger, Paul; Reinisch, David; Vogl, Christoph; et al. (Energy and Environmental Science, 2020)
Although recent years have brought significant progress within the field of electrochemical conversion of CO(2)and CO to value-added chemicals, many more challenges need to be overcome for this technology to be implemented on an industrial level. Rational design of catalyst materials that would enable selective production of desired products at industrially relevant current densities (>200 mA cm(-2)) is most certainly one of them. Here, we introduce Ag2Cu2O3, a mixed-metal oxide, as a starting template material for efficient electroreduction of CO to C(2+)products. By combining results from electrochemical real-time mass spectrometry (EC-RTMS), XRD and XPS we confirmed the template nature of Ag(2)Cu(2)O(3)andin situformation of a fully reduced CuAg bimetallic material during the first minutes of electrolysis. Electrochemical screening of the catalyst revealed significantly varying product distributions when CO2(CO2RR) and CO (CORR) where used as feed gases. During CORR, a faradaic efficiency close to 92% towards C(2+)products at 600 mA cm(-2)was achieved. On the other hand, during CO2RR, CO was found to be the main product under all tested current densities, reaching a maximum faradaic efficiency of 68%. XPS valence band spectra of the bimetallic surface originating from Ag(2)Cu(2)O(3)showed that its d-band electronic structure is noticeably different compared to metallic Ag and Cu, a finding we link to the observed product distributions. Finally, additional microscopy characterization techniques were used to investigate the observed surface reconstruction of the catalyst material under reaction conditions.
CRIS-Team WoS Importer:2020-10-02

Electrochemical Real-Time Mass Spectrometry (EC-RTMS): Monitoring Electrochemical Reaction Products in Real Time - Khanipour, Peyman; Löffler, Mario; Reichert, Andreas; Haase, Felix T.; Mayrhofer, Karl; Katsounaros, Ioannis (Angewandte Chemie International Edition, 2019)
Methods that provide real-time information are essential to resolve transients occurring at dynamic interfaces. Now a powerful method is presented that enables the time- and potential-resolved characterization of liquid and gaseous products of electrochemical reactions shortly after their formation. To demonstrate its extraordinary potential, the electrochemical real time mass spectrometry (EC-RTMS) approach is used to determine the products of the CO 2 reduction reaction (CO 2 RR) during potential step or sweep experiments on pristine and in situ anodized copper. The enhanced formation of several C 2+ products over C 1 products is tracked directly after copper anodization, with unprecedented temporal resolution. This new technique creates exciting new opportunities for resolving processes that occur at short timescales and eventually for guiding the design of new, robust catalysts for selective electrosynthesis under dynamic operation.
CRIS-Team Scopus Importer:2019-05-02
Keywords: analytical chemistry; CO2; electrochemistry; mass spectrometry; time-resolved product analysis

Probing CO2 Reduction Pathways for Copper Catalysis Using an Ionic Liquid as a Chemical Trapping Agent - Zhang, Gui Rong; Straub, Sascha Dominic; Shen, Liu Liu; Hermans, Yannick; Schmatz, Patrick; Reichert, Andreas; Hofmann, Jan P.; Katsounaros, Ioannis; Etzold, Bastian J.M. (Angewandte Chemie, 2020)
The key to fully leveraging the potential of the electrochemical CO2 reduction reaction (CO2RR) to achieve a sustainable solar-power-based economy is the development of high-performance electrocatalysts. The development process relies heavily on trial and error methods due to poor mechanistic understanding of the reaction. Demonstrated here is that ionic liquids (ILs) can be employed as a chemical trapping agent to probe CO2RR mechanistic pathways. This method is implemented by introducing a small amount of an IL ([BMIm][NTf2]) to a copper foam catalyst, on which a wide range of CO2RR products, including formate, CO, alcohols, and hydrocarbons, can be produced. The IL can selectively suppress the formation of ethylene, ethanol and n-propanol while having little impact on others. Thus, reaction networks leading to various products can be disentangled. The results shed new light on the mechanistic understanding of the CO2RR, and provide guidelines for modulating the CO2RR properties. Chemical trapping using an IL adds to the toolbox to deduce the mechanistic understanding of electrocatalysis and could be applied to other reactions as well.
CRIS-Team Scopus Importer:2020-09-11
Keywords: CO; copper; foams; ionic liquids; reaction mechanisms